ANALISIS PEMBELAJARAN LITERASI KEUANGAN MELALUI KONTEN VIDEO: TINJAUAN PADA SHORT VIDEO TIKTOK - Haerunisa -; Mochammad Reza Putra Nugroho; Meisya Putri Izati; Salmadila Ramadhanty; Buyung Firmansyah (Politeknik Bisnis Indonesia, 2024)
The purpose of this study is to analyze the application of education to the public regarding financial literacy through video content on social media on the TikTok platform. The method used in this research is a qualitative method. Qualitative method is a method used to solve research problems through observation activities in the form of narratives. The results of research using the observation method by analyzing Raymond Chin's video content on the TikTok platform. This study shows that Raymond Chin has met the indicators analyzed, including Raymond Chin's ability to provide fast and relevant information to the audience using hand gestures, voice intonation that makes his performance not look monotonous, and uses informal language and often uses English and slang to attract the audience. This makes Ryamond Chin very popular for audiences who want to learn and have an interest in financial literacy. In his video content, Raymond Chin is able to invite the audience to feel what he says so that it can generate interest to make the audience care about the messenger from him.